1991
DOI: 10.1159/000186435
|View full text |Cite
|
Sign up to set email alerts
|

Immune Deficiency in Uremia: Interleukin-2 Production and Responsiveness and Interleukin-2 Receptor Expression and Release

Abstract: We have studied the role of interleukin-2 (IL-2) and its receptors in the impaired in vitro lymphocyte response characteristic of hemodialysis patients treated by means of cuprophane membranes. The proliferative response of T lymphocytes as well as T-cell-dependent B cell proliferation after stimulation with mitogens was significantly reduced in hemodialysis patients. The in vitro production of IL-2 after such stimulation in parallel cultures was found to be similar in patients and in controls. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 26 publications
4
12
1
Order By: Relevance
“…In vitro soluble IL-2R released from mitogen-stimulated human peripheral blood lymphocytes can bind IL-2 and inhibit IL-2-dependent cell proliferation [35]. Our findings of increased sIL-2R levels in plasma are consistent with those of others [34, 36, 37]. IL-2Rα seems to undergo substantial renal clearance [34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In vitro soluble IL-2R released from mitogen-stimulated human peripheral blood lymphocytes can bind IL-2 and inhibit IL-2-dependent cell proliferation [35]. Our findings of increased sIL-2R levels in plasma are consistent with those of others [34, 36, 37]. IL-2Rα seems to undergo substantial renal clearance [34].…”
Section: Discussionsupporting
confidence: 88%
“…As T cells produce IL-2, the decreased number of CD4+ cells partly explains the suppressed IL-2 production [33]. However, another report [34]showed that the in vitro production of IL-2 is similar in T cells from patients and controls. In vitro soluble IL-2R released from mitogen-stimulated human peripheral blood lymphocytes can bind IL-2 and inhibit IL-2-dependent cell proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…In particular polymorphonuclear granulocytes and/or monocytes, are probably more prominent in the effector phase of active WG. Although retention of slL-2R with impaired renal function has been suggested [38], our findings can not be explained as a result of progressive renal failure during major disease activity, since there was no correlation between sIL-2R levels in those patients and creatinine clearance (data not shown). Others also have suggested overproduction of sIL-2R as a more important factor than metabolic retention to explain the observed high levels of sIL-2R in patients with renal vasculitis [37].…”
Section: Discussioncontrasting
confidence: 53%
“…While an increased CD25 expression in T cells of HD patients has been observed previously [28][29][30][31][32][33], the role of uraemia versus dialysis in this abnormality remain to be elucidated in more detail. In our study, the increased CD25 expression in CD4 + T cells was found in all uraemic patients, irrespective of dialysis modality, suggesting an influence of uraemia per se.…”
Section: Discussionmentioning
confidence: 80%